Survival outcomes of parotid carcinomas treated with surgery and adjuvant radiation therapy - Kazi, Maliha; Warner, Laura; Rajgor, Amar; Iqbal, Shahid (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2026)
Background: Parotid cancers are a diverse histological group of cancers involving the parotid gland with varying effects of prognostic factors on treatment outcomes. The effect of adjuvant radiotherapy on the outcome in parotid cancers has always been debated in the past. The objective of current study was to measure the effect of prognostic factors and the survival outcomes of patients with primary parotid cancers treated with surgery and adjuvant radiotherapy. Methods: From January 2010 to December 2023, a total of 61 patients treated at Freeman Hospital, were included in the analysis. Data was collected and stratified according to age, gender, tumour staging, surgical margins, lymphovascular invasion (LVI), peri-neural invasion (PNI), extra nodal extension (ENE) and recurrence rate. All patients treated with surgery and adjuvant radiotherapy were included in the study. Patients with incomplete data, distant metastasis or those lost to follow up were excluded. The OS, DSS and RFS rates based on surgical margins, LVI, PNI and ENE were calculated. Results: The 5-year OS, DSS and RFS were 72.6%, 79.6% and 77.7%, respectively. Positive surgical margins did not influence the survival outcome in comparison to close or clear margins. Lower survival rates were noted for patients with ENE, although not reaching statistical significance. Conclusion: Though retrospective in nature, our study provides valuable information that close or involved surgical margins do not adversely affect the outcome for parotid cancers treated with surgery and adjuvant radiotherapy and that surgical re-resection might not be indicated in this patient population.